Estado cognitivo e incontinência urinária em idosos institucionalizados - Gonçalves, Gabrieli Rodrigues (2019)
The objective of this study was to verify the relationship between the cognitive status and the occurrence of urinary incontinence (UI) in institutionalized elderly. This is an observational, cross-sectional study with a quantitative approach. Data were collected between November 2017 and January 2018. The elderly were investigated, ranging in age from 60 to 90 years old, of both sexes, living in two long-term institutions for the elderly (LTIE) of a municipality in the south of Brazil. The research instruments were composed of the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) and the Mini Mental State Examination (MMSE). Statistical analyzes were performed using SPSS 17.0 software. To verify the normality of the data, the Shapiro-Wilk test was performed. For the correlation of variables, the Spearman Correlation Coefficient was used, assuming a significance level of 5%. Thirtysix elderly, 29 (80.55%) males and 7 (19.45%) females, with mean age of 69.64 ± 5.87 years, were evaluated. The mean MMSE score of the total study participants was 24.78 ± 4.12 points. The mean ICIQ-SF score was 5.36 ± 6.97 points. Regarding the occurrence of UI, 18 (50%) elderly reported losing urine, 14 (77.77%) men and 4 (22.23%) women. No correlation was observed between ICIQ-SF and MMSE scores. There was no correlation between cognitive status and UI in the elderly sample of this study. It is possible that several uninvestigated factors are involved in this outcome.